High-functioning autism patients share similar but more severe impairments in verbal theory of mind than schizophrenia patients. Issue 8 (18th September 2017) - Tin, L. N. W.; Lui, S. S. Y.; Ho, K. K. Y.; Hung, K. S. Y.; Wang, Y.; Yeung, H. K. H.; Wong, T. Y.; Lam, S. M.; Chan, R. C. K.; Cheung, E. F. C.
Abstract: Background: Evidence suggests that autism and schizophrenia share similarities in genetic, neuropsychological and behavioural aspects. Although both disorders are associated with theory of mind (ToM) impairments, a few studies have directly compared ToM between autism patients and schizophrenia patients. This study aimed to investigate to what extent high-functioning autism patients and schizophrenia patients share and differ in ToM performance. Methods: Thirty high-functioning autism patients, 30 schizophrenia patients and 30 healthy individuals were recruited. Participants were matched in age, gender and estimated intelligence quotient. The verbal-based Faux Pas Task and the visual-based Yoni Task were utilised to examine first- and higher-order, affective and cognitive ToM. The task/item difficulty of two paradigms was examined using mixed model analyses of variance (ANOVAs). Multiple ANOVAs and mixed model ANOVAs were used to examine group differences in ToM. Results: The Faux Pas Task was more difficult than the Yoni Task. High-functioning autism patients showed more severely impaired verbal-based ToM in the Faux Pas Task, but shared similar visual-based ToM impairments in the Yoni Task with schizophrenia patients. Conclusions: The findings that individuals with high-functioning autism shared similar but more severe impairments in verbal ToM than individuals with schizophrenia support the autism–schizophrenia continuum. The finding that verbal-based but not visual-based ToM was more impaired in high-functioning autism patients than schizophrenia patients could be attributable to the varied task/item difficulty between the two paradigms.